Frequency of uterine sarcomas in patients admitted for uterine fibroid surgery - Mettler, Liselotte (J Turk Ger Gynecol Assoc, 2017)
OBJECTIVE: To estimate the frequency of unsuspected uterine sarcoma identified postoperatively in women undergoing surgery for presumed benign uterine fibroids at a single university hospital. MATERIAL AND METHODS: This was a retrospective single-center study; the records of all 2275 patients with uterine fibroids and uterine sarcomas from 2003 to 2015 were reviewed. Descriptive statistics were used to analyze demographic and clinical characteristics. To calculate confidence intervals (CIs), the Clopper-Pearson Exact method was applied. RESULTS: Preoperatively, 2269 patients had presumed benign uterine fibroids, and six patients had suspected uterine sarcoma. Among the 2269 patients who underwent surgery for presumed uterine fibroids, endometrial stromal sarcoma was histopathologically revealed in only one patient [0.044%, 95% CI: (0.001-0.25)] after laparoscopic subtotal hysterectomy with morcellation. All six patients who were preoperatively diagnosed having uterine sarcoma underwent direct conventional cancer treatment. Histopathologic analyses confirmed four cases of uterine leiomyosarcoma, one high-grade undifferentiated uterine sarcoma, and one embryonal rhabdomyosarcoma. Altogether, seven women were diagnosed as having uterine sarcomas over this twelve-year period. CONCLUSION: In our institution, the frequency of unsuspected uterine sarcomas was 1/2269 (0.044%) among women who underwent myomectomies and hysterectomies to treat presumed benign uterine fibroids.